Study of air quality through suspended particles determination. Issue 1 (1st February 2022) - Miloştean, D; Flori, M
Abstract: The suspended and settleable particles which exist permanently in the atmosphere have their concentration variation depending on weather conditions, traffic in the collecting area, industrial activities, etc. It is known that once these particles pollute the atmosphere can affect human health so, their collection by efficient filtration air systems is needed in order to proper evaluate them. In this paper the short-term concentration of the suspended particles from air is determined in the collection point located inside the Faculty of Engineering Hunedoara (Romania), in the vicinity of the road. The sampling was done in months May and June of year 2020, during three time intervals. Obtained minimum and maximum suspended particles concentrations were 13.43 &b.mu;g/m 3 and 83.96 &b.mu;g/m 3, respectively.